Biofloc-Based Enhanced Survival of Litopenaeus vannamei Upon AHPND-Causing Vibrio parahaemolyticus Challenge Is Partially Mediated by Reduced Expression of Its Virulence Genes - Kumar, Vikash; Wille, Mathieu; Lourenço, Tânia Margarida; Bossier, Peter (Frontiers in Microbiology, 2020)
The biofloc system is a relatively a new aquaculture technology that offers a practical solution to maintain culture water quality by recycling nutrients and, in particular nitrogen, from unconsumed feed, faecal materials and metabolic products. There are reports, suggesting that a biofloc system improves the health status and resistance of shrimps against microbial infection, yet the mode of action involved remains unclear. This study aimed to unravel the underlying mechanism behind the protective effect of a biofloc system using Litopenaeus vannamei and AHPND-causing Vibrio parahaemolyticus M0904 strain as a host-pathogen model. The results showed that a biofloc system maintained at a C/N ratio of 15, improves the water quality and contributes to the nutrition of cultured animals as bioflocs might serve as an additional protein source. Furthermore, the study demonstrated that the biofloc system enhances the survival of L. vannamei upon challenge with a V. parahaemolyticus AHPND strain. Remarkably, the results highlights that in the biofloc system, AHPND-causing V. parahaemolyticus possibly switch from free-living virulent planktonic phenotype to a non-virulent biofilm phenotype, as demonstrated by a decreased transcription of flagella-related motility genes (flaA, CheR and fliS), Pir toxin (PirBVP) and AHPND plasmid genes (ORF14) and increased expression of the phenotype switching marker AlkPhoX gene in both in vitro and in vivo conditions. Taken together, results suggest that biofloc steer phenotype switching, contributing to the decreased virulence of V. parahaemolyticus AHPND strain towards shrimp postlarvae. This information reinforces our understanding about AHPND in a biofloc setting and opens the possibility to combat AHPND not only by trying to eliminate the AHPND-causing V. parahaemolyticus from the system but rather to steer the phenotypic switch.